Trauma-informed services and trauma-specific care for Indigenous Australian children - Judy Atkinson
This paper examines how childhood trauma experienced by Indigenous children can be overcome by appropriate interventions.IntroductionWhile many Indigenous and non-Indigenous Australian children grow up in safe homes and live in safe communities, there are some who do not. In the case of Indigenous children, some families and communities are unable to, or are still working to, heal the trauma of past events, including displacement from Country, institutionalisation and abuse. The Stolen Generations also represent a significant cause of trauma. In 2008, an estimated 8% of Indigenous people aged 15 and over reported being removed from their natural family and 38% had relatives who had been removed from their natural family. This trauma can pass to children (inter-generational trauma).Indigenous children may also experience a range of distressing life events including illness and accidents, hospitalisation or death of close family members, exposure to violence, family disintegration (with kin networks fragmented due to forced removals, relationship breakdown and possibly incarceration) and financial stress.Experiencing trauma in childhood can have severe and long-lasting effects; effects that can be overcome by appropriate interventions. This resource sheet examines these effects and explores how they can be tackled. It focuses on the design and delivery of trauma-informed and trauma-specific children’s services and care